A "cracking" school culture: leading resource exploitation during implementation of a national reform. Issue 5 (7th April 2021) - Tamir, Emanuel; Ganon-Shilon, Sherry
Abstract : Purpose: The study explores characteristics of strong school cultures through principals' exploitation of additional resources within implementation of a national reform. Design/methodology/approach: An interpretive approach was utilized to analyze qualitative data from semi-structured interviews with 35 Israeli high school principals who implemented a national reform in state and religious-state schools from all school districts. Findings: The article presents four types of cracking cultures led by the principals: (1) a school values-based culture, such as respect; (2) a caring culture based on trust and a positive atmosphere; (3) a maintenance achievement-oriented culture; and (4) a creative culture that supports the teachers and takes risks in using resources beyond their intended purpose. Originality/value: Exploring principals' exploitation of resources within a cracking culture may promote school improvement and innovation during national reform implementation.